PENINGKATAN KEMAMPUAN PENGELOLAAN WEBLOG DENGAN KONTEN INTERNET SEHAT SEBAGAI SARANA PUBLIKASI DAN INFORMASI PADA SISWA SMA NEGERI 2 SEMARANG - Galet Guntoro Setiaji; April Firman Daru; Saifur Rohman Cholil (TEMATIK, 2020)
Community Service Activities (PkM) "Increasing the Capability of Management of Healthy Weblogs with Internet Content as a Means of Publication and Information for Students of Semarang 2 High School" involving partners of High School Middle School students in the city of Semarang. Many school students have not used the weblog to provide information and publications about activities related to learning, school organization activities and other activities. In this activity, partners will be given training in making weblogs with healthy internet content by the PKM team tailored to the level of needs and resources of each partner. At the end of this activity, it is expected that all students who take part in the training can create a weblog by filling out healthy internet content for the better so that it will improve  the  ability  of  publications  and  information  to  internet  users  as  a  form  of  community  service. The purpose of this service is to increase the ability of weblogs to share knowledge, publications and information of  students by creating a healthy internet on the weblog.